Pemetaan Risiko Bencana Longsor Sebagai Upaya Penanggulangan Bencana di Kecamatan Tembalang Kota Semarang - Fitriani, Nur; Heri, Tjahjono; Budi, Sanjoto Tjaturahono (Geo-Image, 2018)
This Research aims for knowing the level of landslide risk and for knowing how much knowledge of citizens, then to know how disaster management is done in Tembalang district, Semarang city. To create landslide risk map was based on the Regulation of the Head of National Disaster Management Agency Number 02, 2012, defined by Hazard, Vulnerability, an Capacity factors.In determining hazard, vulnerability, and capacity, each has sub factors to determine it along with the scores. Based on this research in Tembalang district, the villages have high level of risk are Jangli, Tandang, Sambiroto, Mangunharjo, Tembalang, Bulusan, Sendangmulyo, and Meteseh. In Tembalang district, most of the villagers already have the basic knowledge of landslide, and in their handling about landslide they used to build talud together.